Unveiling the Mysteries: Human Communication with Jinn - Myth or Reality? - Muktarruddin; Khatibah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
Al-Qur'an regulates all forms of communication: with Allah, fellow humans, and spirits/jinn. In human Communication with Jinn, Allah reported through the story of the fall of the Prophet Adam and Siti Hawa from heaven after consuming the khuldi fruit. Both slipped because of a jinn's instigation in Allah's name. It proves that apart from Jinn and humans being able to communicate, the potential for deception is also genuine. Therefore, this research aims to explain the communication/relationship between humans and Jinn. This qualitative research method uses a thematic approach to verses from Al-Qur'an relating to human and Jinn communication. Data was from literature by analyzing books and scientific journals with similar themes. Data analysis uses the transcendental communication/magical communication paradigm. The research results show that Al-Qur'an explained that human Communication with Jinn exists. However, it does not need to be developed. Human and Jinn communication has many negative effects. The negative impact is that humans will always be filled with anxiety, will tend to commit crimes, and will be classified as the actions of people who are misguided and disobedient to Allah. Some Jinns are believers, and some are unbelievers. However, humans cannot differentiate them because they are supernatural beings. Communication between humans and Jinn generally occurs through ruqyah syar'iyyah rituals to improve the community's economy and shamanic practices.